Congenital lobar emphysema - Sarıoğlu, Tayyar; Saylam, Argun; Aytaç, Aydın; Sarıkayalar, Fikriye; Çağlar, Melda; Alp, Mete (The Turkish Journal of Pediatrics, 1983)
A series of 15 patients with congenital lobar emphysema is presented. Lobectomy was performed in 14 cases and pneumonectomy in 1. Four patients died due to various causes (26.6%). An average follow-up of 2 years in the surviving individuals showed satisfactory results. We believe that surgical resection of the involved lobe(s) is the only effective method of treatment for this congenital malformation.